posted by .

how do you multiply and simplify 3*^3sqrt of 5y^3* 2* ^3sqrt of 50y^4

## Similar Questions

1. ### Algebra

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
2. ### algebra

Why is it important to simplify radical expressions before adding or subtracting?
3. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
4. ### Pre-Cal(Urgent)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
5. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
7. ### Math

Use rational exponents to simplify the radical. If rational exponents appear after simplifying, write the answer in radical notation. 3sqrt(2)/ 5sqrt(2)
8. ### Algebra 2/Trig

I've done every other single question besides this one. (There was 12). I'm stumped and would really appreciate some help! I have to simplify this: 5/3sqrt(3-4) I am not sure if you have to conjugate the denominator and multiply it …
9. ### Sums-Calc

find the upper and lower bounds for definite integral sign, a=1, b=6, sqrt(x) dx. partitions are as follow: x0=1, x1= 3, x2=6 of the interval [1,6] upper sum: 3sqrt(3) + 3sqrt(6) lower sum: 3sqrt(3) + 3 but this is incorrect. can someone …
10. ### Calculus

1) yy'-e^x= 0, and y=4 when x=0 means that: A)y=x-lnx^2+4 B)y^2=4x^2+3 C)y=-2x+1/2x^3 D)y^2=2e^x+14 E)1/2ln|x^2+4|+6 2) The rate of change of P with respect to t is directly proportional to (10-t) and inversely proportional to the …

More Similar Questions

Post a New Question